2022
DOI: 10.3389/fimmu.2022.827242
|View full text |Cite
|
Sign up to set email alerts
|

Insights From Early Clinical Trials Assessing Response to mRNA SARS-CoV-2 Vaccination in Immunocompromised Patients

Abstract: It is critical to protect immunocompromised patients against COVID-19 with effective SARS-CoV-2 vaccination as they have an increased risk of developing severe disease. This is challenging, however, since effective mRNA vaccination requires the successful cooperation of several components of the innate and adaptive immune systems, both of which can be severely affected/deficient in immunocompromised people. In this article, we first review current knowledge on the immunobiology of SARS-COV-2 mRNA vaccination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 164 publications
(177 reference statements)
1
6
0
Order By: Relevance
“…While studies have shown immune responses in some immunocompromised individuals after 2 doses of an mRNA vaccine [22] , others have reported immune responses in substantially fewer individuals with immune deficiency after 2 doses compared with healthy individuals [23] . Earlier immunogenicity studies reported lower seroconversion rates after COVID-19 vaccination in immunocompromised patients, compared to immunocompetent individuals [11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While studies have shown immune responses in some immunocompromised individuals after 2 doses of an mRNA vaccine [22] , others have reported immune responses in substantially fewer individuals with immune deficiency after 2 doses compared with healthy individuals [23] . Earlier immunogenicity studies reported lower seroconversion rates after COVID-19 vaccination in immunocompromised patients, compared to immunocompetent individuals [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both allogeneic HSCT and anti-CD20 therapy have been associated with increased duration of viral shedding and COVID-19 relapses, which are linked to virus replication and mutation [39] , [40] . Further, although early administration of COVID-19 monoclonal antibody (mAb) treatment can improve COVID-19 outcomes of immunosuppressed individuals infected with SARS-CoV-2 [22] , mAb can also lead to selection of mAb resistant variants [41] . As such, COVID-19 vaccines remain critical to provide adequate protection for these populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocompromised patients are at high risk of severe COVID-19. Since they might not elicit an adequate immune response after vaccination, passive immunization using ex-vivo produced neutralizing antibodies is one of the key therapeutic options in such populations 1 . Monoclonal anti-spike antibodies have shown a great risk reduction of hospitalization or death in immunocompetent patients 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, utility of these antibody-based tests may be reduced in some individuals due to low or absent antibody titers [9][10][11][12]. Furthermore, serologic testing is not informative for some patients, such as those undergoing iatrogenic B-cell depletion or with primary humoral immunodeficiencies [13,14].…”
Section: Introductionmentioning
confidence: 99%